A grammar of the Ugaritic language - Sivan, Daniel. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2001)
Ugaritic, discovered in 1929, is a North-West Semitic language, documented on clay tablets (about 1250 texts) and dated from the period between the 14th and the 12th centuries B.C.E. The documents are of various types: literary, administrative, lexicological. Numerous Ugaritic tablets contain portions of a poetic cycle pertaining to the Ugaritic pantheon. Another part, the administrative documents shed light on the organization of Ugarit, thus contributing greatly to our understanding of the history and culture of the biblical and North-West Semitic world. This important reference work, a revised and translated edition of the author's Hebrew publication (Beer Sheva, 1993), deals with the phonology, morphology and syntax of Ugaritic. The book contains also an appendix with text selections.